Hot-rolled H-beams with high strength, high toughness, and low-temperature resistance for floating oil tankers, and method for manufacturing the same.
Patent Information
- Application Number
- JP2026517656
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-22
- Filing Date
- 2023-11-16
- Publication Date
- 2026-10-14
AI Technical Summary
【0034】 本発明の技術案の利点は、以下の通りである。
Smart Images

Figure 2026534214000001_ABST
Abstract
Description
TECHNICAL FIELD
[0001] [CROSS-REFERENCE TO RELATED APPLICATIONS] This application claims the priority of the Chinese patent application No. 2023112308667 entitled "High-strength, high-toughness, low-temperature resistant hot-rolled H-section steel for floating oil transport vessels and manufacturing method thereof", filed on September 22, 2023, which is incorporated herein by reference in its entirety.
[0002] The present invention belongs to the technical field of metallurgy and rolling, and specifically relates to a high-strength, high-toughness, low-temperature resistant hot-rolled H-section steel for floating oil transport vessels and a manufacturing method thereof.
BACKGROUND ART
[0003] Floating oil transport vessels are high-end large-scale marine engineering equipment for exploiting deep-sea oil and gas resources, which can realize the exploitation, processing, storage and transportation of energy such as offshore oil and natural gas, and are known as "offshore oil processing factories". Different from relatively fixed offshore oil platforms, floating oil transport vessels are not only capable of exploiting oil and storing and transporting crude oil products, but also are large-scale offshore oil production bases integrating residential accommodation and production command. They can quickly arrive at designated locations to carry out oil and gas development, and have unique advantages such as short construction period and strong maneuverability, making them suitable for oil and gas development operations in multiple sea areas around the world.
[0004] As oil and gas extraction expands from conventional sea areas to complex regions with extreme temperatures and frigid conditions, the production, storage, discharge, and transportation of floating oil tankers face increasingly complex challenges. Therefore, the manufacture of large oil tankers demands stricter material upgrades and the adoption of new materials and technologies to ensure maintenance for over 30 years without dry-docking, minimizing maintenance costs. The manufacture of the superstructure requires a large quantity of hot-rolled H-beams. With increasing demands, there is a pressing need for high-performance hot-rolled H-beams to replace conventional low-level H-beams, achieving weight reduction while guaranteeing high stability and reliability. To adapt to the service environments of complex regions such as extreme frigid conditions, higher demands are placed on the low-temperature impact toughness of the steel. The required H-beams need to have a strength of 420 MPa or higher, and a relatively low ductile-brittle transition temperature. The low-temperature resistance of the material must reach at least E-grade, and ideally, F-grade. Therefore, with the increase in the number of floating oil tankers being manufactured, the demand for hot-rolled H-beams with high strength levels of 420 MPa or higher, which also possess low-temperature resistance, is rising simultaneously.
[0005] Currently, Chinese hot-rolled H-beam manufacturers have successively developed E-grade low-temperature resistant H-beams with a yield strength of 355 MPa or higher, achieving commercial development and widespread adoption. There are also differences in production methods in the production lines; generally, they are manufactured using a combination of composite microalloying with added Nb, V, and Ti and thermomechanically controlled rolling, and patent applications highlight the differences in manufacturing methods between different companies and production lines.
[0006] The invention patent with application number CN201510788520.8 discloses a 420 MPa class high-strength low-yield-ratio H-beam and a method for manufacturing the same. The chemical composition of the H-beam is, by weight percent, C 0.11~0.15%, Si 0.20~0.35%, Mn 1.35~1.50%, P≦0.035%, S≦0.025%, Cu 0.25-0.30%, Cr 0.40-0.45%, Ni 0.20-0.30%, Nb 0.20-0.30%, with the remainder being iron and trace amounts of impurities. The present invention achieves a low-yield-ratio H-beam with a yield strength greater than 427 MPa, a tensile strength greater than 641 MPa, and a yield ratio of 0.64~0.67. This patent involves adding elements such as Ni, Nb, and Cu for use in specific high-corrosion-resistant environments. The manufacturing process is affected by the Cu element, increasing the probability of cracking in the flange portion of H-beams under high final rolling temperatures, requiring surface polishing, and resulting in a relatively low yield. Furthermore, the addition of Cr and Cu elements easily leads to the formation of abnormal structures, and the material lacks clear yield, making it difficult to guarantee safety performance.
[0007] The invention patent with application number CN201510498771.2 provides a 420 MPa class hot-rolled H-beam with excellent low-temperature toughness and a method for producing the same, the composition being C 0.06~0.12%, Si 0.20~0.40%, Mn 1.20~1.60%, P≦0.015%, S≦0.010%, V 0.050~0.070%, Ni 0.10~0.20%, N 0.0050~0.0100%, with the remainder being Fe and unavoidable impurities. Compared to conventional technologies, this invention develops a 420 MPa hot-rolled H-beam with superior overall performance through a rational V, Ni, and N component design and a rolling cooling control process, achieving a yield strength ReH of 440-520 MPa, a tensile strength Rm of 550-650 MPa, an elongation A of A ≥ 22%, and a low-temperature impact toughness KV2 at -40°C of ≥ 100 J. The cooling control in this patent employs a two-stage process: a first-stage rapid cooling followed by a second-stage air cooling. Special cooling equipment is required to meet the above manufacturing requirements. The produced 420 MPa class hot-rolled H-beam with excellent low-temperature toughness is required to meet a Z-direction performance of 40-65%. The process design is intended for large-shaped steel products of 15 mm or more using irregularly shaped slabs, and is not suitable for the manufacture of small and medium-sized thin-flange H-beam products.
[0008] The authorized invention patent with application number 202110818559.5 provides a 420 MPa class hot-rolled low-temperature resistant H-beam and a method for manufacturing the same. The chemical composition of the H-beam is, by weight percent, C: 0.08%~0.10%, Si≦0.2%, Mn: 1.25%~1.45%, V: 0.03%~0.045%, Ti: 0.015%~0.025%, Cr: 0.15%~0.30%, A1s: 0.02%~0.04%, N: 0.007%~0.01%, P≦0.008%, S≦0.005%, O≦0.004%, with the remainder being Fe and unavoidable impurities. This invention, in the rolling of small and medium-sized H-beams using rectangular slabs, takes into account the characteristic of thin flanges and employs a low carbon content suitable for normalized rolling, along with a component design for V microalloying. By adding an appropriate amount of chromium (Cr) to control the cooling rate, it avoids the formation of abnormal structures such as Widmanstätten, which would worsen the low-temperature toughness of the steel. This invention realizes a production process design for small and medium-sized H-beams that achieves E-grade low-temperature toughness under conditions where the molten iron is controlled to a low phosphorus (P) content. However, precise operation is required for cost control and process implementation, so there is a certain degree of difficulty. Adding a certain amount of Ti can easily adversely affect impact toughness due to TiN precipitation.
[0009] The above patent relates to 420 MPa class H-beams and their manufacturing technology, and there are high demands for molten iron control and post-rolling cooling equipment. Therefore, to meet the demand for H-beams for floating ships, when rolling small and medium-sized H-beams using a compact universal rolling mill with a short process time, it is necessary to employ normalized rolling under high final rolling temperature conditions and design the composition and transformation microstructure to achieve a yield strength of 420 MPa class while lowering the ductile-brittle transition temperature. At the same time, with the overall improvement in yield strength, the uniformity and stability of the microstructure of the upper and lower flanges and head and tail sections must be improved as soon as possible. The strength difference between the web and flanges must be controlled within an appropriate range so as not to affect the overall fatigue performance of the member. Furthermore, because floating vessels constantly travel through various complex environments and polar sea areas, the structural steel used in their onboard structures must have a relatively low low-temperature ductility-to-brittle transition temperature. This ensures good low-temperature impact toughness and avoids the serious waste of energy and resources caused by premature failure of steel structural components of the hull due to low-temperature brittle fracture, which leads to increased maintenance costs and a significantly shorter service life for floating vessels. [Overview of the project] [Problems that the invention aims to solve]
[0010] To meet the demand for high-strength, high-temperature-toughness H-beams for floating oil tankers in complex environments, we design a hot-rolled H-beam with high strength, high toughness, and low-temperature resistance, and a manufacturing method thereof, based on the hull structure characteristics, exclusively for the production of structural members for floating hulls. This H-beam, based on the concept of environmental protection, highlights lightweighting technology, achieving an overall reduction in the transportation cost of floating vessels, improving material utilization efficiency, reducing the number of H-beams per vessel by more than 500 tons, and achieving a weight reduction target of 15-30% in the floating oil tanker structure, providing product and technical support for steel structures for hull modules. [Means for solving the problem]
[0011] The technical proposal of this invention is as follows:
[0012] A hot-rolled H-beam with high strength, high toughness, and low-temperature resistance for floating oil tankers, and a method for manufacturing the same, wherein the chemical composition is, by weight percentage (%), C: 0.07~0.11, Si ≤ 0.2, Mn: 1.5~1.9, V: 0.06~0.10, Nb: 0.02~0.05, Ni: 0.1~0.4, B: 0.001~0.002, Alt: 0.025~0.045, P ≤ 0.015, S ≤ 0.006, N: 0.01~0.015, O ≤ 0.003, with the remainder being Fe and unavoidable impurities.
[0013] H-beams manufactured while meeting these chemical composition requirements can more reliably meet the requirements for impact toughness at polar temperatures.
[0014] This invention is particularly suitable for small to medium-sized H-shaped steel products with a flange thickness of 15 mm or less, but is not limited to products conforming to the above specifications.
[0015] The design principle for the main chemical elements in the high-strength hot-rolled H-beam described in the present invention is as follows:
[0016] Carbon: In order for hot-rolled H-beams for floating ships to reach a strength of 420 MPa and meet the requirement for low-temperature resistance at -40°C, the substrate of the prototype steel has a pearlite and ferrite ultrafine grain structure, with a grain size of at least grade 9 according to the grain size standards. Furthermore, the carbon participates in the formation of a certain number of nanoscale vanadium-containing carbon nitrides. Small H-beams have relatively high compression and relatively high carbon content, making them prone to abnormal structures and the formation of a large amount of pearlite structure. Therefore, the carbon content is controlled within the range of 0.07 to 0.11%.
[0017] Manganese: In hot-rolled H-beams, manganese (Mn) can stabilize the austenitic structure, increase the hardenability of the steel, and improve its strength. At the same time, Mn is an element that is prone to segregation, and because the cross-section of useful H-beams is complex, there are differences in deformation and structural transformation in different parts, which can easily lead to significant differences in performance. To reduce segregation while ensuring strength, it is preferable to have a Mn content of 1.5% or more. However, too much Mn can easily cause abnormal structures. Considering all factors, in this invention, the Mn content in the steel is controlled to be between 1.5% and 2.0%.
[0018] Sulfur: The sulfur element forms Mn and MnS during the manufacturing process of H-beams. Intermittently present inclusions resulting from the manufacturing process severely degrade the low-temperature toughness of the steel, and the ratio of Mn to S affects the mechanical properties and surface defect occurrence of the steel. Too much sulfur easily forms a large amount of MnS inclusions, degrading the workability, and it is preferable to limit the S content to 0.006% or less.
[0019] Aluminum (Al) is used in the manufacturing process as a strong deoxygenating element and as an element that produces AlN, thereby refining the crystal grains. This ensures that the oxygen content in the steel is kept as low as possible, reducing the probability of spherical inclusion formation. Furthermore, AlN precipitates, which consist of aluminum and nitrogen in the steel, can refine the crystal grains and improve the strength of the steel. Therefore, in this invention, the aluminum content is controlled to 0.025-0.045%.
[0020] Niobium (Nb) can form second-phase particles such as NbC and NbN in steel. During the recrystallization rolling process, NbC and NbN play a role in pinning dislocations and inhibiting grain growth, significantly increasing the recrystallization time. The characteristic of niobium in steel is that it improves the austenite recrystallization temperature, expands the temperature range of the non-recrystallized region, promotes deformation of austenite grains and "accumulation" of defects, and ultimately achieves the goal of refining ferrite grains. In addition, precipitated Nb(C,N) plays a role in inhibiting the growth of austenite grains during heating, ultimately achieving the goal of refining the structure in which austenite has been displaced. Therefore, in the rolling of small and medium-sized steel sections using low-carbon steel, the goal of grain refinement can be achieved by adding a small amount of niobium and controlling the rolling process in a normal steel section rolling mill, controlling the Nb content to 0.02-0.05%.
[0021] Vanadium: As a strong carbonitride-forming element, V carbonitrides play a role in precipitation strengthening. VN alloys can serve as nucleating particles for ferrite and pearlite structures, contributing to grain refinement. VC is generated during the later stages of rolling and cooling, and is generally present in steel at a nanoscale, playing a role in precipitation strengthening. Vanadium-containing steel precipitates during the later stages of rolling, resulting in lower rolling deformation resistance and reducing rolling load. For low-temperature resistant steel with a yield strength of 420 MPa, controlling the V content to 0.06-0.10% achieves grain refinement and nano-strengthening precipitation.
[0022] Nickel: The element Ni can play a role in improving impact toughness in steel, and can significantly expand the process window, especially in batch production processes. Considering factors such as cost, the amount of Ni is controlled within the range of 0.1-0.4%.
[0023] Nitrogen: The N element in steel forms a VN alloy with V to exert a precipitation strengthening effect and improve the strength. Under high temperature conditions, it can form NbN with Nb to inhibit grain growth. However, if the N content is too high, quality defects on the surface of the cast slab are prone to occur, such as transverse cracks; if the nitrogen content is low, the precipitation effect of the formed VN particles is poor, so the present invention requires the nitrogen content to be 0.01~0.015%.
[0024] Boron: The main role of B is to improve the hardenability of steel, and the hardenability of steel can be improved by adding a small amount of boron. The indirect effect of boron delaying the γ-α transformation is to improve the solubility of alloy elements and reduce the chemical heterogeneity of the continuous cast slab. Boron has strong affinity with nitrogen and oxygen, and the aging phenomenon of steel can be eliminated by adding an appropriate amount of boron element. A certain amount of B element is added to the steel of the present invention, the cooling rate of the steel is properly controlled to avoid abnormal microstructure, and the addition range is 0.001~0.002%.
[0025] Oxygen: A high oxygen content tends to form large-particle oxides with strong oxidizing elements, thereby reducing the toughness and plasticity of the section steel, and the present invention requires the oxygen content to be ≤0.003%.
[0026] The floating marine hot-rolled H-beam has a yield strength ≥ 440MPa, a tensile strength ≥ 520MPa, an elongation ≥ 18%, and an impact energy at -60°C ≥ 150J.
[0027] The present invention further provides a method for manufacturing the above-mentioned 420MPa yield strength grade H-beam. The manufacturing method includes the following steps: hot metal pretreatment → 50t electric furnace smelting → ladle argon blowing → LF refining → VD degassing → rectangular continuous cast slab → slow cooling of the continuous cast slab in a slow cooling pit → heating in a heating furnace → BD rough rolling → compact TM semi-continuous rolling on the section steel line → inter-stand cooling + lower flange water cooling after rolling → dense slow cooling in a cooling bed.
[0028] In the rolling process, the soaking temperature of the heating furnace is 1190~1220°C, the holding time of the cast slab in the furnace is 180~240min, and the rough rolling in the rolling process usually adopts 7~9 passes of reciprocating rolling. The finish rolling adopts 5 passes of continuous rolling, the rolling start temperature of finish rolling is 960~1000°C, all the water-cooled members between the finish rolling stands are opened, and the final rolling temperature of finish rolling is 780~850°C. A steel reversing machine is used to perform steel reversing operation between rough rolling and finish rolling, and the temperature is decreased for 20~50s based on the temperature detection result, so as to ensure that the entry temperature drops to an appropriate range. To ensure the temperature control of final rolling, the reduction ratio of the last pass of finish rolling is 8%~15%, and sufficient cooling after finish rolling is beneficial to precipitate the carbonitride of V and exert the precipitation strengthening effect.
[0029] The present invention realizes the industrial production of 420MPa grade high-strength, high-toughness floating offshore H-section steel products for ships under different reduction ratio conditions, through the addition of Nb and the design of V microalloying process, in combination with the characteristics of semi-continuous rolling of section steel.
[0030] All processes not mentioned in the present invention can adopt the prior art.
[0031] In order to ensure the high consistency and uniformity of the microstructure and properties of the upper and lower flanges of the produced H-section steel, the present invention performs precise design on the process aspect to meet the performance requirements.
[0032] Regarding the characteristics of the equipment for the short-process semi-continuous rolling process, the distance between the roughing mill and the finish mill is around 60 meters. This short distance cannot meet the rapid cooling demand of the intermediate slab, and at the same time, the temperature difference between the upper and lower flanges is large, reaching up to 70°C. The rolling process needs to be optimized and improved. Based on the control characteristics of the heating and rolling process, a steel inversion operation is necessary between the roughing and finish mills, and the upper and lower flanges of the H-shaped steel are inverted before the start of finish rolling. However, since the length of the cast slab increases significantly after rough rolling, the intermediate slab temperature can reach 1050°C, and uneven steel inversion easily leads to twisting of the rolled member, increasing the difficulty of jamming during the rolling process when entering finish rolling, causing steel jamming. Therefore, to meet the demand for steel inversion, a short-time, high-speed steel inversion operation is performed on the intermediate slab between finish rolling and rough rolling.
[0033] To improve the yield strength of H-beams for floating ships, with both the upper and lower flanges reaching 420 MPa or higher, a composite microalloying operation is employed, and in this invention, strength is improved mainly by the VN alloying method. Furthermore, considering the high requirement for steel purity, LF+VD is used in the smelting process of a 50-ton electric furnace for degassing. However, after VD degassing, the nitrogen content decreases significantly, and it is necessary to perform a nitrogen increase treatment according to the actual nitrogen content. The method of nitrogen increase is to add a certain amount of manganese nitride core wire and adjust it according to the nitrogen content. [Effects of the Invention]
[0034] The advantages of the proposed technology of this invention are as follows:
[0035] 1. In rolling medium-sized H-beams using rectangular slabs, taking into account the characteristics of varying compression ratios and thin flanges, a low carbon content suitable for normalized rolling is adopted, and the composition of composite microalloys using Nb·V is designed. Furthermore, by controlling the N content during the refining process, the precipitation of VN is improved, thereby meeting the strength and toughness requirements of products of different specifications. As a result, high-strength, tough hot-rolled H-beams of 420 MPa or higher, which can be stably controlled in a hot-rolling H-beam rolling mill, are obtained.
[0036] 2. In the refining process, LF+VD is used to control the purity of the molten steel. Since the nitrogen content decreases after VD degassing, a nitrogen increase treatment is performed according to the N content to improve the precipitation strengthening effect of VN. The method of nitrogen increase is to add 20-50 meter manganese nitride core wires to increase the nitrogen content in the steel and maintain it in the range of 0.01-0.015%.
[0037] 3. During the rolling process, a dedicated steel reversing machine is used between rough rolling and finish rolling to perform a steel reversal operation, significantly reducing the temperature difference between the upper and lower flanges to 25°C or less. Based on the intermediate temperature detection results, the temperature is appropriately reduced on the roller conveyor and maintained for 20-50 seconds. After this, the temperature of the rolled member is controlled to within the range of 960-1000°C, and then placed in the finish rolling mill for 5 passes of continuous rolling. This improves the low-temperature toughness of the steel and maintains a high level of impact energy greater than 150J at -60°C conditions.
[0038] 4. Ensure uniform performance by opening all cooling water between stands and after rolling, controlling the final rolling temperature between 780 and 850°C, reducing the temperature difference between the upper and lower flanges to 20°C or less, and controlling the yield strength difference between the upper and lower flanges to within 15 MPa.
[0039] 5. The substrate structure of the H-shaped steel is fine pearlite + protereminate ferrite, with the grain size controlled within the range of 9 to 11 grade. The stably precipitated second phase grains are mainly V(C,N), resulting in high microstructure uniformity and good control of the aging strengthening effect.
[0040] 6. Through the synergistic effect of ultrafine structure of the substrate and precipitation strengthening mechanism mainly involving VN precipitation, a yield strength of 420 MPa is achieved for hot-rolled H-beams for floating ships, and a low-temperature impact energy greater than 150 J at -60°C is obtained, resulting in a favorable effect.
[0041] 7. The H-shaped steel of the present invention has a low carbon equivalent, thus ensuring that it possesses both high strength and high toughness, as well as excellent weldability.
[0042] 8. According to the present invention, the overall strength of H-shaped steel can be improved, and the steel plate can be given excellent fatigue resistance, thereby enabling the steel plate according to the present invention to fully meet the usage requirements of ship and floating oil tanker users. [Brief explanation of the drawing]
[0043] [Figure 1] This is a metallurgical diagram (×100) of a high-toughness, low-temperature resistant H-shaped steel beam with a yield strength of 420 MPa, manufactured according to the present invention. [Figure 2] This is a metallurgical diagram (×200) of a high-toughness, low-temperature resistant H-beam steel with a yield strength of 420 MPa, manufactured according to the present invention. [Figure 3] This is a metallurgical diagram (×500) of a high-toughness, low-temperature resistant H-shaped steel with a yield strength of 420 MPa, manufactured according to the present invention. [Figure 4] These are the ductile-brittle transition curves of HE200B steel at different temperatures. [Modes for carrying out the invention]
[0044] The continuously cast slabs in the following examples are all manufactured using the following process. Based on the set chemical composition range, a certain amount of scrap steel is blended with blast furnace molten iron as a raw material, and the content of C, Si, Mn, S, P, etc. is adjusted and microalloying is performed by electric furnace smelting and LF+VD refining. After the composition reaches the target value, continuous casting is performed, and the cast slab is directly heated or soaked. The manufacturing steps for Examples 1-4 are as follows.
[0045] Molten iron pretreatment → 50t electric furnace smelting → ladle argon injection → LF refining → VD degassing → rectangular continuous casting slab → continuous casting slab slow cooling in a slow cooling pit → heating in a heating furnace → BD rough rolling → compact TM semi-continuous rolling in the structural steel line → cooling between stands + water cooling of the lower flange after rolling → dense slow cooling on a cooling bed. Structural steel line rolling includes two stages of rolling: rough rolling and finish rolling. The hot rolling process is mainly controlled by temperature control, and the final rolling temperature is measured at the midpoint between the upper and lower flanges on the outside of the flange. After rolling, the rolled material is cooled by piling it up on a cooling bed.
[0046] Example 1: The chemical composition of high-strength, high-toughness H-beams was prepared according to the following weight percentages (%): C: 0.07, Si: 0.15, Mn: 1.90, V: 0.10, Nb: 0.025, Ni: 0.11, B: 0.0011, Alt: 0.025, P: 0.013, S: 0.005, N: 0.014, O: 0.0025, with the remainder being iron (Fe) and CeV: 0.41. The prepared raw materials were smelted in a 50-ton electric furnace, and in the degassing process of the refining VD furnace, a 21-meter manganese nitride core wire was inserted to increase nitrogen content, and then the material was continuously cast into rectangular continuous casting slabs measuring 240 mm × 375 mm × 5800 mm. In the rolling process, the continuously cast slab was heated to 1210°C and held for 190 minutes. After being discharged from the BD, the steel was inverted, and after the temperature dropped for 30 seconds, it was placed in a sizing tandem rolling mill and rolled. The starting temperature for the finish rolling was controlled to 1000°C, and the temperature difference between the finish rolling stands was controlled by water cooling. The final rolling temperature for the finish rolling was controlled to 815°C for the upper flange and 830°C for the lower flange, and the rolling standard was European standard HE200B. Ultimately, an H-beam with high strength and high toughness was obtained and straightening treatment was performed.
[0047] The test data results for the product's mechanical properties were as follows: ReH: 443 MPa, Rm: 530 MPa, δ: 20%, and -60℃ Akv: average 203 J.
[0048] Example 2: The chemical composition of high-strength, high-toughness H-beams was prepared according to the following weight percentages (%): C: 0.08, Si: 0.19, Mn: 1.85, V: 0.08, Nb: 0.021, Ni: 0.18, B: 0.0013, Alt: 0.035, P: 0.014, S: 0.003, N: 0.013, O: 0.003, with the remainder being iron (Fe) and CeV: 0.41. The prepared raw materials were smelted in a 50-ton electric furnace, and in the degassing process of the refining VD furnace, a 19-meter manganese nitride core wire was inserted to increase nitrogen content, and then the material was continuously cast into rectangular continuous casting slabs measuring 240 mm × 375 mm × 5800 mm. In the rolling process, the continuous casting slab was heated to 1200°C and held for 200 minutes. After being discharged from the BD, the steel was inverted using an automatic steel inversion machine. After the temperature dropped for 25 seconds, it was placed in a sizing tandem rolling mill for rolling. The starting temperature for the finish rolling was controlled to 990°C, and the temperature difference between the finish rolling stands was controlled by water cooling. The final rolling temperature for the finish rolling was controlled to 810°C for the upper flange and 826°C for the lower flange, and the rolling standard was European standard HE160B. Ultimately, an H-beam with high strength and toughness was obtained and straightened.
[0049] The test results for the product's mechanical properties were as follows: ReH: 452 MPa, Rm: 542 MPa, δ: 21%, and -60℃ Akv impact energy: average 221 J.
[0050] Example 3: The chemical composition of high-strength, high-toughness H-beams was prepared according to the following weight percentages (%): C:0.10, Si:0.20, Mn:1.65, V:0.09, Nb:0.023, Ni:0.28, B:0.0016, Alt:0.03, P:0.013, S:0.003, N:0.012, O:0.003, with the remainder being iron (Fe) and Cev:0.40. The prepared raw materials were smelted in a 50-ton electric furnace, and in the degassing process of the refining VD furnace, a 23-meter manganese nitride core wire was inserted to increase nitrogen content, and then the material was continuously cast into rectangular continuous casting slabs measuring 240 mm × 375 mm × 5800 mm. In the rolling process, the continuously cast slab was heated to 1205°C and held at that temperature for 220 minutes. After being discharged from the BD, the upper and lower flanges were reversed using an automatic steel reversing machine. After the temperature dropped for 26 seconds, it was placed in a sizing tandem rolling mill for rolling. The starting temperature for the finish rolling was controlled to 985°C, and the temperature difference between the finish rolling stands was controlled by water cooling. The final rolling temperatures for the finish rolling were controlled to 805°C for the upper flange and 816°C for the lower flange, and the rolling standard was European standard HE220A. Ultimately, an H-beam with high strength and high toughness was obtained and straightening treatment was performed.
[0051] The test results for the product's mechanical properties were as follows: ReH: 462 MPa, Rm: 553 MPa, δ: 19%, and -60℃ Akv impact energy: average 189 J.
[0052] Example 4: The chemical composition of high-strength, high-toughness H-beams was prepared according to the following weight percentages (%): C:0.10, Si:0.20, Mn:1.51, V:0.07, Nb:0.020, Ni:0.37, B:0.0012, Alt:0.03, P:0.012, S:0.003, N:0.011, O:0.003, with the remainder being iron (Fe) and CeV:0.38. The prepared raw materials were smelted in a 50-ton electric furnace, and in the degassing process of the refining VD furnace, an 18-meter manganese nitride core wire was inserted to increase nitrogen content, and then the material was continuously cast into rectangular continuous casting slabs measuring 240 mm × 375 mm × 5800 mm. In the rolling process, the continuously cast slab was heated to 1190°C and held for 240 minutes. After being discharged from the BD, the upper and lower flanges were reversed using an automatic steel reversing machine. After the temperature dropped for 36 seconds, it was placed in a sizing tandem rolling mill for rolling. The starting temperature for the finish rolling was controlled to 980°C, and the temperature difference between the finish rolling stands was controlled by water cooling. The final rolling temperatures for the finish rolling were controlled to 795°C for the upper flange and 805°C for the lower flange, and the rolling standard was European standard HE180A. Ultimately, an H-beam with high strength and toughness was obtained and straightened.
[0053] The test results for the product's mechanical properties were as follows: ReH: 456 MPa, Rm: 543 MPa, δ: 23%, and -60℃ Akv impact energy: average 225 J.
[0054] The structural steel obtained in Examples 1-4 was tested using a PLG-100C high-frequency fatigue testing machine. The loading method was axial dynamic loading, and N=10 was used with the lifting method. 7 The conditional fatigue limits of the material during the cycle were measured at a frequency of approximately 92 Hz. According to the measurement results, the conditional fatigue limits of the web and flange of the H-beam in Example 1 were 595 MPa and 545 MPa, respectively. The conditional fatigue limits of the web and flange of the H-beam in Example 2 were 575 MPa and 543 MPa, respectively. The conditional fatigue limits of the web and flange of the H-beam in Example 3 were 602 MPa and 558 MPa, respectively. The conditional fatigue limits of the web and flange of the H-beam in Example 4 were 585 MPa and 546 MPa, respectively.
[0055] The test specimens followed the standard BS EN ISO 377-1997, "Sampling location and preparation of test specimens for mechanical property testing." The test methods for yield strength, tensile strength, and elongation followed the standard ISO 6892-1-2009, "Room temperature tensile testing method for metallic materials." The impact energy test method followed the standard ISO 148-1, "Charpy pendulum impact test for metallic materials." Examples 1-4 of the present invention maintained a yield strength of 440 MPa or higher, exhibited good elongation performance, and had high impact energy at -60°C, achieving an overall F-class level. As shown in Figure 4, the ductile-brittle transition temperature was extremely low, making it suitable for floating vessels to operate in different marine environments and significantly improving the fatigue life of the material. It can meet the operating conditions for shipbuilding and marine engineering components in cryogenic environments and is applicable to the manufacture of support structural components that require high low-temperature toughness, such as floating oil tankers, polar offshore oil platforms, and ocean-going vessels.
[0056] As can be seen from Figures 1, 2, and 3, the microstructure of the present invention is an ultrafine pearlite + ferrite structure, and the temperature difference between the upper and lower flanges is controlled to within 15°C, thereby ensuring that the strength of the upper and lower flanges is controlled to 15 MPa or less. The ultrafine grain structure meets the requirements for manufacturing H-beams with a strength of 420 MPa, satisfies the strength index, and also improves low-temperature toughness.
[0057] All upper and lower limits and interval values of the process parameters (e.g., temperature, time, etc.) of the present invention can be used to implement this method, and therefore, examples will not be listed individually here.
[0058] Any aspects not described in detail in this invention can be addressed by applying prior art knowledge in the field.
[0059] Finally, it should be noted that the above embodiments are not limiting, but merely illustrate the technical concept of the present invention. Although the present invention has been described in detail with reference to the embodiments, it should be understood that any modifications or equivalent substitutions to the technical concept of the present invention by those skilled in the art will not deviate from the spirit and scope of the technical concept of the present invention and will all be included within the scope of the claims of the present invention.
Claims
1. A hot-rolled H-beam with high strength, high toughness, and low-temperature resistance for floating oil tankers, The hot-rolled H-beam for floating oil tankers is characterized by having high strength, high toughness, and low-temperature resistance, with a chemical composition of the following weight percent: C: 0.07-0.11%, Si ≤ 0.2%, Mn: 1.5-1.9%, V: 0.06-0.10%, Nb: 0.02-0.05%, Ni: 0.1-0.4%, B: 0.001-0.002%, Alt: 0.025-0.045%, P ≤ 0.015%, S ≤ 0.006%, N: 0.01-0.015%, O ≤ 0.003%, with the remainder being Fe and unavoidable impurities.
2. The hot-rolled H-shaped steel for a floating oil tanker according to claim 1, characterized in that the flange thickness of the H-shaped steel is less than 15 mm.
3. The hot-rolled H-beam having high strength, high toughness, and low-temperature resistance, as described above, is characterized in that it has a yield strength of ≥ 440 MPa, a tensile strength of ≥ 520 MPa, an elongation of ≥ 18%, and an impact energy of ≥ 150 J at -60°C, as described in claim 1, for use in a floating oil tanker.
4. The hot-rolled H-shaped steel for floating oil tankers according to claim 1, characterized in that the substrate structure of the H-shaped steel is fine pearlite + proterite, and the grain size is controlled within the range of 9 to 11.
5. A method for manufacturing hot-rolled H-beams with high strength, high toughness, and low-temperature resistance for floating oil tankers, A method for manufacturing hot-rolled H-beams with high strength, high toughness, and low-temperature resistance for floating oil tankers, including the steps of: molten iron pretreatment → electric furnace smelting → ladle argon injection → LF refining → VD degassing → rectangular continuous casting slab → continuous casting slab slow cooling in a slow cooling pit → heating in a heating furnace → BD rough rolling → compact™ semi-continuous rolling in a structural steel line → cooling between stands + water cooling of the lower flange after rolling → dense slow cooling on a cooling bed.
6. The manufacturing method according to claim 5, characterized in that, during the rolling process, the soaking temperature of the heating furnace is 1190 to 1220°C, the holding time of the casting slab in the furnace is 180 to 240 min, and rough rolling employs reciprocating rolling of 7 to 9 passes.
7. The manufacturing method according to claim 5, characterized in that the finish rolling employs continuous rolling, the starting temperature for the finish rolling is 960 to 1000°C, all water-cooling members between the finish rolling stands are open, and the final rolling temperature for the finish rolling is 780 to 850°C.
8. The manufacturing method according to claim 5, characterized in that a steel inversion operation is performed using a steel inversion machine between rough rolling and finish rolling, and after the temperature has dropped for 20 to 50 seconds based on the temperature detection result, the temperature of the rolled member is controlled to be within the range of 960 to 1000°C, and then placed in a finish rolling mill for continuous rolling.
9. The manufacturing method according to claim 5, characterized in that the compression ratio of the final pass of finish rolling is 8% to 15%, and sufficient cooling after finish rolling is advantageous for precipitating carbonitrides of V and exhibiting a precipitation strengthening effect.
10. The manufacturing method according to claim 5, characterized in that LF + VD is used in the refining process to control the purity of the molten steel, and since the nitrogen content decreases after VD degassing, the precipitation strengthening effect of VN is improved, so a nitrogen increase treatment is carried out according to the N content, and the method of increasing the nitrogen is to add a 20 to 50 meter manganese nitride core wire to increase the nitrogen content in the steel and maintain it in the range of 0.01 to 0.015%.